Prototype perception of physically active peers: result from a study among Hungarian university students - Noemi Tari-Keresztes; Bettina Piko; Himanshu Gupta; Andrew Decelis; Aniko Dely-Palinkas; Zsuzsanna Fejes (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
Introduction: Previous studies argued the role of social prototypes in making desicisions on healthy and unhealthy behaviors. Positive images associated with a certain behavior might increase the possibility of developing the behavior. While most of the studies focused on health risk behaviors, health promoting behaviors have been less investigated yet. However, young adults are more conscious about the social images associated with health behaviors compared with their younger equivalents; much of the relevant research has been conducted with the latter groups. Purpose: The main aim of this study was to (1) examine how university students perceive their physically active peers, (2) map the adjectives associated with the 'physically active peers' prototypes, (3) identify respondents' categories based on their prototype perception, and (4) detect relationships between social images, sociodemographic variables, sporting habits and social attitudes. Material and Method: Cross-sectional, self-report data were obtained from a convenience sample of 515 respondents aged 18-31 years via a survey with students from a Hungarian university. Result: Cluster analyses detected three independent clusters: "Negative" image" group, "Positive appearance" group, "Positive appearance and personality" group. Age, gender, self-assessed SES, sporting friends, social support, social network, Internet use, competitiveness and the need to belonging seemed to make a difference along these groups of social images. Conclusion: Our findings suggested that social variables may play a moderate role in university students' sport-related prototype formation.